The Influence of Problem-Based Learning (PBL) Model on Student Learning Outcomes on the Concept of Measurement - Indah Oktaviani; Tirtawaty Abdjul; Mursalin (Postgraduate, University of Mataram, 2024)
Problem-based learning (PBL) is a learning model that focuses on problems and solving. This research aims to describe the influence of the PBL model on student learning outcomes on the concepts of measurement. This method is experimental and replication class. The research is carried out in class VII on Madrasah Tsanawiyah school at MTs Ma'arif Tolangohula for the 2023/2024 academic year. The research design used is one group pretest-posttest. Test the research hypothesis using the t-test where, before carrying out the t-test, the data is tested first using the requirements test, namely the normality test and the N-gain test. Based on the research results, it is known that learning using the PBL model in the experimental class obtained a post-test score of 85.18, replication 1 of 80.71, and replication 2 of 80.24, for the t-test in the post-test the experimental class obtained Tcount of 5.174 and Ttable of 2.131, for the replication 1 obtained Tcount of 3.133 and Ttable of 2.131, and replication 2 obtained Tcount of 4.287 and Ttable of 2.131. This shows that the PBL model has the influence of improving student learning outcomes on the concept of measurement.